Consequences of bad storage and incorrect disposal of medicines (Research, Society and Development, 2023)
The ease of access to medicines has always contributed to the increase in inadequate storage and incorrect disposal, including in completely inappropriate places. Self-medication, since the beginning, has been a common practice in society, also causing harm to the environment. Drug residues contain resistant chemical components that can contaminate soil and water. Storage in easily accessible places poses the risk of incorrect use, resulting in poisoning. The groups most susceptible to these problems are the elderly and children. Therefore, the objective of this study is to describe the main consequences of improper storage and incorrect disposal of medicines, as well as the problems that this practice entails in terms of environmental imbalance and the emergence of antibiotic-resistant bacteria, resulting in public health problems. Through an integrative literature review, factors that may contribute to greater access by the population to information on how to properly proceed with the conservation and conscious disposal of this waste will be discussed.